POTENTIAL GEO-DISTRIBUTION OF PINUS SIBIRICA DEMONSTRATED BY CLIMATIC SIMILARITY BETWEEN WESTERN SIBERIA AND NORTHEAST CHINA - S. Shah; Q. Liu; J. Yu; S. Meng; G. Zhou; Y. Li; D. Khan; T. Ullah; A. Ahmad ，S. Saeed; A. Mannan (Journal of Animal and Plant Sciences, 2019)
The spatio-temporal distribution of forests is related to climate. Pinus sibirica is a native species in areas subject to continental temperate cold climate that favors its growth. This study was carried out with the aim of evaluating the climatic suitability of northeast and northwest China for the introduction of Pinus sibirica. For this purpose, climate of the northeast and northwest China was compared with the climate of Western Siberia (Russia). The Climatic data was obtained from NMKI Climate explorer and China meteorological administration. The Tukey Pairwise Comparison test found that Mohe weather station in northeast China shows (-4.7 °C, -3.26 °C, -5.31 °C and -3.9 °C) resemblance in temperature with three of western Siberian stations where Pinus sibirica is distributed in association with Larix sibirica and Picea obovata. The annual mean precipitation for all the weather stations including Mohe and Huma, China was more than 420 – 609 mm. This specie is also found to grow in various elevations in Western Siberia from 45 to 25 m in Altai Mountains, and from 300 to 700 m in Daxing’ anling Mountains. In conclusion, climatic regimes in terms of temperature and precipitation in Daxing’ anling Mountains allow the introduction of the Pinus sibirica into northeast China.
Keywords: Pinus sibirica; Northeastern China; Northwestern China